Adult Hodgkin’s Lymphoma in Indonesian National Cancer Center Hospital: An Observational Study - Tadjoedin, Hilman (Indonesian Journal of Cancer, 2024)
Background: Hodgkin’s lymphoma (HL) is a malignancy of lymphatic glands whose incidence is higher in Asia than in other continents and it is highly curable amongst other hematological malignancies. Our study aims to establish distribution data among HL patients in the Indonesian National Cancer Hospital.Method: A cohort retrospective was conducted from 2017 to 2021 on HL patients. Data on demographic and clinical characteristics were collected and described.Result: From 177 HL subjects, 52.5% were men with a median age of 32 years. B-symptoms occurred in 30.1% of subjects. Most subjects have great performance status (44%) and normal body mass index (39.6%). Comorbidities found were diabetes mellitus (10.3%) and hypertension (8.1%). By hematological examination, lactate dehydrogenase (LDH) level was found 85.7% more than 240 U/dL, hemoglobin (Hb) level 71.6% non-anemic, leukocytosis in 33.5%, and thrombocytosis in 59.4%. The disease stage is mostly in stage 2 (51%), with 19.2% having extra nodal lesions which are commonly found in bone marrow (32.2%). The outcome showed that 69.2% of subjects survived.Conclusion: In general, the majority of subjects were young adult males, with no B-symptoms, great performance status, no comorbidity, elevated LDH levels, normal Hb and white blood cell counts, high platelet counts, and were diagnosed with stage 2 disease. Most patients with Hodgkin’s Lymphoma survived for 5 years.